Integrated resource planning : case of a Bangladesh electric utility - Amin, Md. Ruhul; Shrestha, Ram M.; Lefevre, Thierry; Fujiwara, Okitsugu; Bhattacharya, Sribas C.; Swedish International Development Authority (SIDA) (Bangkok : Asian Institute of Technology, 1995)
This study deals with the optimal capacity expansion planning process by finding the optimal combination of supply side and demand side resources. A model has been developed and has been used as a mixed integer programming (MIP). It captures the changes in system load shape due to implementation of demand side management more accurately than the existing models. Simultaneously integration technique has been used to integrate the supply side and demand side resources. Some considerations such as environmental cost, reduction of air pollution emission constraints, transmission and distribution losses are the main aspects of the model. The model used in this study is the extension of the existing model. Some important features have been included with the previous model such as penetration rate of DSM options, fuel resource limitations and reduction of air pollution emission constraints. Also the model has been applied here, considers DSM options of industrial sector of Bangladesh unlike the previous one that was used only for residential sector of Calcutta, India. This model has been applied for the optimal expansion plan for Bangladesh Power Development Board and has been evaluated by analyzing three scenarios. From the solution of both traditional resource planning (TRP) and integrated resource planning, schedule of generation expansion have been found out. Besides these, optimal supply and demand side resource mix, optimal load despatching schedule, supply costs, revenue requirements, environmental emissions etc. have been determined to compare IRP and TRP. The results obtained from the model found to be realistic and logical. Simultaneously it emphasizes the requirement of IRP in developing countries like Bangladesh. Some important findings from the study using the model can be referred as the reduction of electricity cost and increase of the electricity price for IRP, IRP may need not always reduce emission of air pollution as compared to TRP and reduction of air pollution by generation mix is not always possible. Finally, marginal cost of supply from the results of the model is also shown. Marginal cost based pricing are rarely used in developing countries due to socio-political reason and the effects of this type of efficient pricing should be critically examined and compared with the existing pricing.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1995
Keywords: Electric utilities -- Bangladesh